Summarised report on the mission to Spain of 21-29 January 1937 : for the members of the IFTU Executive, the LSI Bureau and the International Solidarity Fund - Labour and Socialist International; Schevenels, Walther, b. 1894
1937-02-06 015b_0007_005 292/946/15b/7(v)